2016
DOI: 10.1021/acs.jafc.6b03805
|View full text |Cite
|
Sign up to set email alerts
|

Red Cabbage Microgreens Lower Circulating Low-Density Lipoprotein (LDL), Liver Cholesterol, and Inflammatory Cytokines in Mice Fed a High-Fat Diet

Abstract: Cardiovascular disease (CVD) is the leading cause of death in the United States, and hypercholesterolemia is a major risk factor. Population studies, as well as animal and intervention studies, support the consumption of a variety of vegetables as a means to reduce CVD risk through modulation of hypercholesterolemia. Microgreens of a variety of vegetables and herbs have been reported to be more nutrient dense compared to their mature counterparts. However, little is known about the effectiveness of microgreens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 50 publications
(72 reference statements)
3
74
0
2
Order By: Relevance
“…Though the health impacts of microgreens were not assessed in the present study, the data from this study will inform future research studies that will evaluate their health impacts. Thus, microgreens were selected based on previous research evaluating their sensory attributes and consumer acceptability, nutritional characteristics, environmental sustainability, and health impacts (Huang et al., 2016; Weber, 2017; Xiao et al., 2012, 2015), as well as researcher interest and input regarding their potential for use as functional foods in reducing disease risk. The microgreen species were chosen due to their potential to provide diversity with respect to their organoleptic properties, as well as micronutrients and bioactive compounds demonstrated to influence human health.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the health impacts of microgreens were not assessed in the present study, the data from this study will inform future research studies that will evaluate their health impacts. Thus, microgreens were selected based on previous research evaluating their sensory attributes and consumer acceptability, nutritional characteristics, environmental sustainability, and health impacts (Huang et al., 2016; Weber, 2017; Xiao et al., 2012, 2015), as well as researcher interest and input regarding their potential for use as functional foods in reducing disease risk. The microgreen species were chosen due to their potential to provide diversity with respect to their organoleptic properties, as well as micronutrients and bioactive compounds demonstrated to influence human health.…”
Section: Methodsmentioning
confidence: 99%
“…Available data indicate that microgreens are rich sources of micronutrients and bioactive compounds, and that the contents of these compounds may be higher than that of their mature counterparts (Choe et al., 2018; Paradiso et al., 2018; Weber, 2017; Xiao, Lester, Luo, & Wang, 2012). In fact, various microgreen species have been shown in several independent investigations to contain higher levels (up to 260‐fold higher in some cases) of certain vitamins (i.e., vitamins C, E, K, and provitamin A/beta‐carotene), minerals (i.e., calcium, magnesium, iron, manganese, zinc, selenium, and molybdenum), and bioactive compounds (i.e., carotenoids, total polyphenols, anthocyanins, glucosinolates, and chlorophyll) than mature counterparts (Huang et al., 2016; Paradiso et al., 2018; Pinto, Almeida, Aguiar, & Ferreira, 2015; Xiao et al., 2012). These data suggest that microgreens can be utilized as a concentrated source of micronutrients and health‐promoting bioactive compounds, though more research is needed to elucidate their nutritional and bioactive compound properties, particularly with respect to the influence of growing practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al. () found that red cabbage microgreen supplementation had health‐promoting effects in mice fed a high fat diet. Supplementation with microgreens attenuated body weight gain, lowered low‐density lipoproteins (LDL) cholesterol levels, reduced hepatic cholesterol ester and triglyceride levels, and inflammatory cytokines.…”
Section: Other Nutritional Facetsmentioning
confidence: 99%
“…Supplementation of high fat diet with mature red cabbage also had beneficial effects but did not reduce triglyceride levels. Interestingly, supplementation of low‐fat diet with red cabbage microgreens raised both low‐density lipoprotein and high‐density lipoprotein cholesterol levels (Huang et al., ).…”
Section: Other Nutritional Facetsmentioning
confidence: 99%